(untitled) (Journal of the College of Basic Education, 2022)
The communications approved by the formal organization reflects the administrative patterns of the deans of the official organizations, which are divided into three official communication sections (Nazl- horizontal - rookie), which is one of the most common types of communication, which requires addressing the subject of regulatory contacts in institutions of higher education colleges to the deans colleges exposure to regulatory contacts to have to learn how the flow of information and the flow of communication in which to overcome the barriers between subordinates and direct their boss, Valotsalat provide management information and data from execution sites to enable them to issue the goal of research is to identify the regulatory communication with the deans of the faculties at the Universities of Baghdad, Mustansiriya , and has been selected sample of deans consisted of (34) Dean of them (23) in the University of Baghdad and 11 in the Al-Mustansiriya University, rely on the search current measure tool (organizational communication) to the areas of organizational communications (downward - Alofiqi- rookie) , using the chi square test at the level of significance (5.,.) to extract the truth to all the paragraphs of the tool under the views of the arbitrators to determine the veracity of the paragraph as longer paragraph honest if the value tabular paragraphs function is statistically greater than (3.84)) show that Fiqra T. the (39) three to their areas obtained the approval of the views Braal (12) and the value of the Chi-square calculated larger than Kai tabular the (384) at the level of significance (0.05) and the degree of freedom (11) has not been deleted or added any paragraph of the paragraphs and the tool formed finalized (39) paragraph scale organizational communications, distributed on three areas downtrend (17) horizontal paragraph (8), paragraph rookie (14) items, consistency of the instrument coefficient (Olvakronbach) for members of the sample reaching stability of the instrument to measure coefficient (organizational communication) to the area of ​​the first contact comes down (0.93) The second area of ​​horizontal communication (0.86) and the third area to call the rookie (0.90) and was an these ratios adequate for the purpose of research, and the findings of the current research for the field (connection downward) has been shown that the arithmetic mean (56 0.4286) degree and a standard deviation of (5.85253) degrees and by comparing this theoretical average of the scale, a (51) degrees and when testing the difference between the Mediterranean using Altaia test of one sample (T- test) it became clear that the T calculated value is (5.488) degree (larger ) Tabulated value of T (42. 2) degree at the level of (0.05) and the degree of freedom (34), show that the computed value of the difference between medium-sized accounts (function) statistically in favor of the deans who practice and use (contact descending), but for the area (contact horizontal) has been shown that the average arithmetic is (27.4000) degrees, a standard deviation of (4.32639) degrees and by comparing this theoretical average of 24 degrees and when testing the difference between the medium and using test Altaia for one sample (T- Test) turned out to be T calculated value (4.649) degree (larger) than the value T-Indexed (2.042) degree at the level of (0.05) and the degree of freedom (34), it shows that the calculated difference between the intermediate value Alhassabeyen (function)statistically significant in favor of the deans who use (horizontal connection) and for the field (Connection rookie) has turned out to be the arithmetic mean is (44.3714) degrees, a standard deviation of (5.95614) degrees and by comparing this theoretical average of 42 degrees and when testing the difference between the medium and using test Altaia for one sample (T- Test) turned out to be T calculated value (2.355) degree is the (largest) of T value Driven (2.042) degree at the level of (0.05) and the degree of freedom (34) show that the calculated difference between the intermediate value Alhassabeyen (function) statistically in favor of the deans who use (connect rookie) and recommended research to benefit from organizational communication and management styles scale as one of the indicators overall quality of the deans evaluate the performance by the officials, a development research we propose to do research on, and regulatory impediments to communication faced by deans management.